Analyzing the Relationship Between City and its influence From Economic Dimension(Case study of Jiroft city) - sedighe mosazade; gholam reza miri; mahmodreza anvari (تحقیقات کاربردی علوم جغرافیایی)
The interaction of city and village is a spatial-spatial and geographical phenomenon, and thus recognizing, discovering and discovering the rules governing it in the context of human-environment interactions is a geographic issue that has a special theoretical and practical significance. Also, considering the role of these relations in the process of development and development of urban and rural centers, in addition to the importance of studying the types of these relationships, the recognition of its socio-cultural, socio-cultural and spatial effects on urban and rural development in the context of sustainable development of rural and urban areas It is very important. This study is to investigate the interrelationship between Jiroft city and surrounding villages through descriptive-analytical method. The method of collecting information based on library and field studies is complete including questionnaire, observation and interview. To do this, out of 1288 villages in the city, we selected 47 randomly selected items and 384 questionnaires were filled in among the villagers. The data were analyzed using Kruskal Wallis & Anova tests (T-test ANOVA) and Pearson & Wilcoxon correlation tests and Wendel Kandal test. . The results of the research show that Jiroft as a middle town and a major pole of agriculture in the south of the country, as well as in terms of aggregation of facilities, capital and manpower in the region, is dominant in the region and its superiority in the area has a two-way relationship with its surrounding villages. On the other hand, the villages under the sphere of influence, also by establishing economic and social-cultural processes, trade relations and investment in the manufacturing, market and urban housing sectors, have the dynamics of the economy and the growth of the city of Jiroft as well as the development in their village as "city dependence" Provided relative.